Fainting schoolgirls wipe A1bn off market value of Gardasil producer. Issue 7605 (7th June 2007) - Chapman, Simon; MacKenzie, Ross
Abstract : Public health workers need to be as vigilant against one-sided media coverage of vaccination as they were against the disinformation spread by the tobacco industry